Efficacy of interferon inducers against Chikungunya virus in vitro - E. V. Otrashevskaja; K. V. Kaa; T. G. Samartseva; A. S. Oksanich; G. M. Ignatyev (Биопрепараты: Профилактика, диагностика, лечение)
Scientific relevance. To date, no specific antivirals have been approved to treat and prevent Chikungunya fever, its complications, and sequelae. Therefore, the development of therapeutic and preventive medicinal products against Chikungunya virus (CHIKV), including interferon inducers, is gaining relevance.Aim. The authors aimed to study the effectiveness of prophylactic administration of an interferon inducer against CHIKV in an in vitro model.Materials and methods. The study used two cell lines (Vero and А549), a CHIKV strain (Nika2021), and an interferon-inducing medicinal product (double-stranded RNA sodium salt) at two doses (250 μg/mL and 500 μg/mL) administered at two schedules: Prevention (4 h prior to the virus challenge) and Emergency Prevention (at the time of the virus challenge). The authors determined the CHIKV titre by its cytopathogenic effect, the CHIKV RNA content by the cycle threshold value in real-time reverse-transcription polymerase chain reaction, and the concentration of cytokines using the enzyme immunoassay method. The study monitored the changes in CHIKV biological activity, CHIKV RNA levels, and the production of interferon-alpha (IFN-α), interferon-gamma (IFN-γ), interleukin-6 (IL-6), and tumour necrosis factor-alpha (TNF-α) in cells over time. The statistical analysis of the resulting data used Microsoft Office Excel 2016 and StatTech.Results. The medicinal product at doses of 250 μg/mL and 500 μg/mL stimulated the production of both IFN-α and IFN-γ (IFN-α to a greater extent than IFN-γ) in both cell lines (in A549 to a greater extent than in Vero). The changes in CHIKV RNA levels with time corresponded to those of the virus titre. In general, CHIKV RNA levels in Vero cells were significantly higher than those in A549 cells (р<0.002 at 250 μg/mL and р<0.0005 at 500 μg/mL). The CHIKV RNA content after preventive interferon inducer administration was significantly lower than that in the control experiment (challenge without administration of the medicinal product) for both doses and both cell lines (р<0.002 for Vero cells; р<0.0003 for А549 cells). The CHIKV RNA content after interferon inducer administration as emergency prevention was significantly lower than that in the control experiment (р<0.05 for Vero cells; р<0.003 for А549 cells). The study demonstrated the efficacy of the interferon inducer against CHIKV and a higher applicability of the A549 cell line to studying antiviral activity in vitro. The authors observed the production of IL-6 and TNF-α by intact cells of both lines.Conclusions. According to the results, the studied interferon inducer has a positive antiviral effect against CHIKV in vitro, with the antiviral effect degree depending on the cell line used. This experimental study demonstrated the need to carefully select the cell line for a study in accordance with its objectives and to evaluate the production of cytokines by a monolayer of cells before stimulation with viruses and/or medicinal products.